2017
DOI: 10.1111/trf.14425
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the applicability and effectiveness of a molecular strategy for identifying weak D and DEL phenotype among D– blood donors of mixed origin exhibiting high frequency of RHD*Ψ

Abstract: The strategy of checking D- donors with RHD PCR followed by exclusion of RHD*Ψ allele has proved efficient in identifying weak-D and DEL phenotype in the Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Our data showed a high prevalence of weak‐D variants with very low antigen density among blood donors, such as weak D type 38 and weak D type 11, which could have been classified as D‐negative if methodologies other than gel was used for direct D typing or if solid phase was not indicated to confirm D‐negative results obtained through tube or microplate hemagglutination. If the chosen method for direct D typing is tube or microplate hemagglutination and sensitive IAT‐methods, such as solid phase, are unavailable to confirm negative results, RHD ‐PCR should be applied to exclude D variant donors which could potentially sensitize D‐negative recipients . Another important observation drawn from our results is that performing the molecular investigation of donors with weak‐D phenotype is an alternative strategy for identifying donors exhibiting RHD*DAR/RHD*DAR and RHD*DAR/RHD*01N.01 genotype.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our data showed a high prevalence of weak‐D variants with very low antigen density among blood donors, such as weak D type 38 and weak D type 11, which could have been classified as D‐negative if methodologies other than gel was used for direct D typing or if solid phase was not indicated to confirm D‐negative results obtained through tube or microplate hemagglutination. If the chosen method for direct D typing is tube or microplate hemagglutination and sensitive IAT‐methods, such as solid phase, are unavailable to confirm negative results, RHD ‐PCR should be applied to exclude D variant donors which could potentially sensitize D‐negative recipients . Another important observation drawn from our results is that performing the molecular investigation of donors with weak‐D phenotype is an alternative strategy for identifying donors exhibiting RHD*DAR/RHD*DAR and RHD*DAR/RHD*01N.01 genotype.…”
Section: Discussionmentioning
confidence: 95%
“…In the immunohematological routine of blood donors, identifying individuals with very weak‐D phenotype is encouraged, as the correspondent RBC unit must be labeled as D‐positive, minimizing the risks of anti‐D development by recipients . The recommendation here is to confirm D‐negative results through sensitive indirect antiglobulin test (IAT) methods and, preferably, RHD ‐PCR . Weak results obtained on the D typing routine of patients may uncover a D‐partial phenotype and, as a consequence, classifying the weak‐D recipients as D‐positive can potentially cause alloimmunization .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have observed that when the molecular report does not provide an interpretation and recommendation, clinical practictioners not experienced in blood group genetics hesitate to interpret RHD genotyping results as D+ or D−. For the purposes of RhIG adminstration and transfusion, interpretation of an RHD genotype requires not only pertinent experience but also knowledge of the history 2,5 as well as the current evolving data [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and literature reports 15,16,[23][24][25][26] of the risks for alloimmunization associated with specific RHD genotypes. 27 Hospital computer systems may require updating to accomodate new requirements, such as the ability to change a prior serologic D typing result, when it is overridden by a different D type based on RHD genotyping results.…”
mentioning
confidence: 99%
“…Studies of serologic RhD‐negative blood donors in Europe and South America have utilized various laboratory‐developed PCR based assays, in either pooled or single donor samples, to identify variant RHD alleles; however, to date, similar studies have not been reported in the United States. Our hospital‐based blood donor center and transfusion service in Los Angeles uses an FDA‐approved single nucleotide polymorphism (SNP) microarray genotyping system (PreciseType HEA, Immucor, N.J.) to predict extended red blood cell phenotype .…”
mentioning
confidence: 99%